Combining subtext application technology and collaborative writing to improve EFL remedial students' writing competence with different learning style. (March 2019) - Sujito; Mahir Muttaqin, Wildan; Kurniasih, Nuning; Bakri, Syamsul; Budi Santosa, Rochmat; Hasan, Moh. Abdul Kholiq; Matin bin Salman, Abdul; Purwanto; Widjajanti, Rina; Istiqomah, Lilik
Abstract: This study was aimed to see the difference of the slow students' writing competence taught using two different strategies: collaborative writing and individual writing by considering learners' learning style. This study used experimental design using factorial design 2x2. Two classes of remedial learners consisted of 30 students for each group was assigned into 2 smaller groups to match with their learning style falling into two classifications: field independent and field dependent learning style. The four groups were given treatment for about 7 meetings. The study revealed three findings. First, learning achievement of the subjects given collaborative writing was higher than the subjects given individual writing. Second, the learning achievement of the subjects having field Independent learning style was higher than the learning achievement of the subject with field dependent learning style. Third, there was no significant interaction between the different analogy types with the subjects' learning style towards writing achievement improvement.